Early career impact of electronic portfolios in music teacher training - Burrack, Frederick W.; Scheib, John W. (My University, 2011)
This descriptive study explored the educational impact of electronic portfolios in a music teacher education program of a mid-sized Midwestern university. Perceptions of 39 practicing teachers who had recently graduated from the program revealed that electronic portfolios provided opportunities to learn about educational technology and were perceived as reflective of effort put forth during university training. Responses also indicated that connection between effective teaching in principle and effective teaching in practice was not clearly evident as had been anticipated. Transfer of portfolio processes into teaching was not apparent. Recommendations are made for teacher education programs employing electronic portfolios.
The impact of electronic portfolios on music teacher preparation
Published title: The impact of electronic portfolios on music teacher preparation
Keywords: Electronic portfolios; Music teacher education; Educational technology